2011
DOI: 10.1111/j.1872-034x.2011.00808.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute presentation of autoimmune hepatitis: Does it exist? A published work review

Abstract: Autoimmune hepatitis (AIH), initially called chronic aggressive hepatitis, is conceptually classified as a primary chronic disease; periportal fibrous expansion and periportal infiltration of mononuclear cells, including plasma cells, have also been considered to be histologically important diagnostic signs of AIH. However, several manuscripts which reported the acute presentation of AIH have been published recently and the reported cases of acute presentation in these manuscripts contained two different clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 39 publications
2
53
0
2
Order By: Relevance
“…Because high serum IgG4 and abundant infiltration of IgG4-bearing plasma cells are prominent characteristics, it was suggested that these findings could define the diagnosis of IgG4-related disease [5]. However, the pathogenesis of IgG4 overexpression remains unclear [6], and it is unknown whether IgG4 is related to the cause of the disease. …”
Section: Introductionmentioning
confidence: 99%
“…Because high serum IgG4 and abundant infiltration of IgG4-bearing plasma cells are prominent characteristics, it was suggested that these findings could define the diagnosis of IgG4-related disease [5]. However, the pathogenesis of IgG4 overexpression remains unclear [6], and it is unknown whether IgG4 is related to the cause of the disease. …”
Section: Introductionmentioning
confidence: 99%
“…Acute presentation is histologically characterized by portal fibrosis and moderate to severe inflammatory cell infiltration and consists of the acute exacerbation phase and acute hepatitis phase, which are characterized by acute exacerbation of chronic liver disease and findings indicative of acute hepatitis, respectively (Table 2) (52). Some patients in the acute hepatitis phase show lower serum levels of IgG and negative autoantibody test results, which make confirming the diagnosis difficult (9,53). The possibility of AIH should always be considered when treating patients with acute hepatitis of an unknown cause.…”
Section: ) Acute Presentationmentioning
confidence: 99%
“…CN itself is a nonspecific finding observed in cases of drug-induced hepatic injury, heart failure, acute viral hepatitis or ischemia and not a histopathological finding of AIH. According to a review by Takahashi et al, CN is found at a frequency of 53-100% in cases of acute hepatitis of AIH, and CN without portal inflammation is particularly characteristic in the acute hepatitis phase of AIH (53). In addition, in some cases of AIH with an acute presentation, heterogeneous low-density areas are observed on plain CT scans and can be used to differentiate the disease from acute hepatic failure of other causes (57,58).…”
Section: ) Acute Presentationmentioning
confidence: 99%
“…We read with great interest the report of Takahashi et al ., 1 which is a review of accumulated literature regarding acute presentation of autoimmune hepatitis (AIH), including fulminant cases. They nicely stated that when a physician encounters a patient with acute hepatitis or fulminant hepatic failure of unknown cause, acute AIH should be kept in mind and an early liver biopsy should be performed, if possible.…”
mentioning
confidence: 99%
“…They nicely stated that when a physician encounters a patient with acute hepatitis or fulminant hepatic failure of unknown cause, acute AIH should be kept in mind and an early liver biopsy should be performed, if possible. Early diagnosis and timely immunosuppression may save many patients 1 . We would like to make some comments regarding the diagnostic and clinical aspects of acute AIH.…”
mentioning
confidence: 99%